Detalhamento acadêmico para magistrados federais como estratégia para aprimorar o conhecimento sobre políticas públicas e evidências em saúde. - Bruno Barcala Reis (2021)
Universal health coverage implies organizing health care and the delivery formats of services and products to citizens. In Brazil, the health system has a principle of universal access, but for more than 30 years, many deficiencies in health care remain. Country observes a day practice of those seeking judicial decisions to determine the provision of health. The National Council of Justice supports the parallel production of scientific evidence to contribute to health rights litigation, despite efforts of the health authorities. The strategy to clarify magistrates about evidence-based-medicine (EBM) and the organization of services, occurs, through courses/conferences, and may be personalized with academic detailing (AD). AD is a method that combines interactive industry outreach with non-commercial, evidence-based information. This study evaluated the AD strategy aimed at federal magistrates. Methods: An AD intervention, combined with an exploratory study describing magistrates' perception of the health authority of prescribers, Anvisa and Conitec; using four decision-making scenarios in a case study, and a satisfaction survey. We developed Key-messages in a workshop. Results: We organize key messages in three bulletins and boards containing EBM information and an algorithm from registration up to incorporation of technologies. From October 2019 to November 2020, we made 61 visits to judges; 64% were men; 36% women; with a mean age of 45 years and 14 years of magistracy. We cover all five regional courts of Brazil, with at least one state from each. The magistrates' satisfaction emphasized the relevance of the content and effectiveness to deepen knowledge. Conclusions: We perceived AD as an instrument for harmonizing the understanding of health policies between magistrates and health services. Listening to magistrates, we observed that they tend to make decisions in the sense of preserving medical authority, providing medicines with public funds, even when in opposition to the public regulatory activity.